Magi: navigating non-hierarchical difference in ecocriticism - Lim, Cheryl Xiao Wei (2017)
Magi: The Labyrinth of Magic is a Japanese manga written by Shinobu Ohtaka, and draws inspiration from the Arabian Nights with its motifs of magic and adventure to create a vast fantasy world, where Alibaba, Aladdin and Morgianna, as they discover the ideal models of kingship and ideology, in order to stop ‘abnormalities’ of the world, “war, poverty [and] discrimination” (Ohtaka 8:180). In doing so, the manga reveals that it partly is concerned with different ways of being that extend beyond the ideological to encompass questions of species. As animalized humans, sentient animals, and a biocentric utopia are presented as the heart of what the manga strives to answer, I argue that it should be analyzed using an ecocritical lens in an attempt to mediate difference between humans and nonhumans so as to understand and that there is a need to view difference nonhierarchically, and a possible way of doing so is to look at animal alterity and subjectivity by critically anthropomorphising animal and thus. mediating on how to we should situate ourselves in relation to, and within, the environment despite being radically different from one another, to provide a guide towards the formation of functional and effective environmental solutions.